2020
DOI: 10.1021/acs.macromol.0c01530
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Agents for Enhanced Performance of Thermosets Prepared via Frontal Ring-Opening Metathesis Polymerization

Abstract: Frontal polymerization (FP) is a self-propagating reaction in which the reactive zone propagates through a monomer solution at a steady velocity. Using FP, polymeric materials are cured rapidly with minimal energy input. Here, we produce high-glass-transitiontemperature thermosets via frontal ring-opening metathesis polymerization (FROMP) of dicyclopentadiene (DCPD) with norbornene-based cross-linkable co-monomers that enable tuning of the cross-link density. The glass-transition temperatures of poly(DCPD) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 37 publications
6
77
0
Order By: Relevance
“…30 mol %). 23 Other reports have noted similar increases in T g with increased crosslinking density or polar functionalization of DCPD itself. 24−26 The addition of cleavable crosslinks to thermosets with permanent, noncleavable crosslinks, however, cannot facilitate chemical deconstruction into soluble products (Figure 1C).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…30 mol %). 23 Other reports have noted similar increases in T g with increased crosslinking density or polar functionalization of DCPD itself. 24−26 The addition of cleavable crosslinks to thermosets with permanent, noncleavable crosslinks, however, cannot facilitate chemical deconstruction into soluble products (Figure 1C).…”
mentioning
confidence: 67%
“…Increasing crosslink density can enhance the thermomechanical properties of thermosets for high-performance applications. , For example, Sottos, Moore, and co-workers reported that the T g of pDCPD prepared by frontal ring-opening metathesis polymerization could be increased by ∼90 °C compared to virgin pDCPD when multifunctional norbornene crosslinkers were doped in at modest levels (ca. 30 mol %) . Other reports have noted similar increases in T g with increased crosslinking density or polar functionalization of DCPD itself. The addition of cleavable crosslinks to thermosets with permanent, noncleavable crosslinks, however, cannot facilitate chemical deconstruction into soluble products (Figure C) .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…[4][5][6][7][8] Recently motivated by the substantial energy and time savings offered by the FP-based approach compared to conventional manufacturing methods, more advances have been made in the development of this technique for thermoset polymers and fiber-reinforced polymer composites (FRPC). 9,10 Simultaneously, theoretical and computational advances have been achieved in the modeling of this process. 11,12 These advances together have enabled a more energy-and timeefficient manufacturing of these materials with mechanical properties comparable to the traditionally manufactured materials used in many industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Research in various aspects of FP‐based manufacturing initiated in the 70s 1–3 and has continued since 4–8 . Recently motivated by the substantial energy and time savings offered by the FP‐based approach compared to conventional manufacturing methods, more advances have been made in the development of this technique for thermoset polymers and fiber‐reinforced polymer composites (FRPC) 9,10 . Simultaneously, theoretical and computational advances have been achieved in the modeling of this process 11,12 .…”
Section: Introductionmentioning
confidence: 99%